SOCIO-HISTORICAL ANALYSIS OF PEACEKEEPING ACTIVITIES OF THE ARMED FORGES OF THE REPUBLIC OF KAZAKHSTAN - Azimzhan Akbota (Theoretical Hypotheses and Empirical Results, 2023)
This article presents a historical overview of the peacekeeping activities of the Armed Forces of the Republic of Kazakhstan aimed at maintaining world peace. The character and image of peacekeepers who went missing and died in the line of duty is a model of patriotism and courage. The author of the article examines the UN Charter and the laws of the Republic of Kazakhstan, paying special attention to the peacekeeping aspect of military doctrine, normative laws are compared with each other. A sociological study (questionnaire, in-depth interview) was conducted among those who served in peacekeeping missions of the Armed Forces of the Republic of Kazakhstan from 1992 to 2020 in Tajikistan and Iraq. The concept of "peacemaking" is explained, and the meaning and role of the peacekeeping mission is determined. The author of the article examines the issues of further development of peacekeeping activities and makes a number of recommendations.